Research on economic inequality. Volume 25 - Bandyopadhyay, Sanghamitra, 1974- (Emerald Publishing Limited, 2017)
This volume contains research on how we measure poverty, inequality and welfare and how we use such measurements to devise policies to deliver social mobility. It contains ten papers, some of which were presented at the third meeting of The Theory and Empirics of Poverty, Inequality and Mobility at Queen Mary University of London, London, October 2016. The volume begins with theoretical issues at the frontier of the literature. Three papers discuss the impact of social welfare policies on poverty measurement, and with innovations on the measurement of relative bipolarisation. Two papers address the conceptualisation of multidimensional poverty by incorporating inequality within the poor, and that of chronic poverty for time dependent analyses, with applications to India and Haiti, and Ethiopia respectively. The second half of the volume consists of empirical contributions, using novel techniques and datasets to investigate the dynamics of poverty and welfare. These studies track the dynamics of poverty using unique datasets for China, the Caucasus and Italy. The volume concludes with investigations about within-household inequalities between siblings due to the unequal effects of conditional cash transfers in Cambodia and a cross-country study on the effect of historical income inequality on entrepreneurship in developing countries.- Resumé vydavatel
Obsahuje index.
Keywords: rovnost (kategorie) -- ekonomické aspekty; chudoba; příjmy; equality -- economic aspects; poverty; income; elektronické knihy; electronic books